2022
DOI: 10.1177/23779608221124417
|View full text |Cite
|
Sign up to set email alerts
|

Use of Automated Infrared Pupillometry to Predict Delirium in the Intensive Care Unit: A Prospective Observational Study

Abstract: Introduction Delirium is an acute state of brain dysfunction prevalent among critically ill patients. Disturbances in the sympathetic neurons, including cholinergic neurons, have been reported to cause delirium by upsetting the balance of neurotransmitter synthesis, release, and inactivation. The cholinergic system mediates pupillary constriction as a response to light stimulation, and this reflex can be measured using automated infrared pupillometry (AIP). The relationship between delirium and AIP parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, inconsistent findings on the use of pupillometry for ICU delirium screening purposes have also been reported. In non-TBI ICU patients, a recent study 18 found no significant association between these 2 PLR variables (pupil constriction percentage and velocity) and delirium but still showed a decrease in values in patients with delirium compared with those without. Notably, other studies conducted during cardiac surgery and postanesthesia care have emphasized the importance of dilation velocity (defined as the recovery phase of the PLR measured in millimeters per second) and the Neurological Pupil index (an algorithm that includes size, latency, constriction velocity, and dilation velocity) as valid predictors of delirium.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, inconsistent findings on the use of pupillometry for ICU delirium screening purposes have also been reported. In non-TBI ICU patients, a recent study 18 found no significant association between these 2 PLR variables (pupil constriction percentage and velocity) and delirium but still showed a decrease in values in patients with delirium compared with those without. Notably, other studies conducted during cardiac surgery and postanesthesia care have emphasized the importance of dilation velocity (defined as the recovery phase of the PLR measured in millimeters per second) and the Neurological Pupil index (an algorithm that includes size, latency, constriction velocity, and dilation velocity) as valid predictors of delirium.…”
Section: Discussionmentioning
confidence: 91%
“…16 However, its application in assessing delirium has only recently been explored, particularly among non-TBI patients. [17][18][19] This technology quantitatively measures the resting pupil diameter and its changes in response to external light stimulation, known as the pupillary light reflex (PLR). 20 The procedure uses an infrared illumination system device with a digital video signal processor, commonly called a video pupillometer.…”
mentioning
confidence: 99%